Al-Taulīd li Muṣṭalaḥāt al-Lugah al-Tasygīliyyah fī Wasā'il al-Tawāṣul al-Ijtimā‘ī: Dirāsah Ṣarfiyyah wa Dalāliyyah - Zelvira, Zelvira; A. Safa, Najamuddin; Harjum, Mohamad (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This research presents a morphological and semantic analytical study of Arabic word formation (neologisms) for operational terms on social media, specifically within the WhatsApp and Instagram applications. The purpose of this research is to identify the morphological and semantic formation patterns of new Arabic terms used in social media interfaces, as well as the methods used to create them. This research utilizes a qualitative descriptive approach. The primary data sources are the Arabic language interfaces of the WhatsApp and Instagram applications. The population and sample of this study comprise the operational terms found within these platforms, specifically 128 terms on WhatsApp and 145 terms on Instagram. Data collection was conducted through observation and documentation techniques. Subsequently, the data were analyzed using morphological and semantic analytical techniques to categorize the neologism patterns. The results of this study reveal 82 distinct, newly coined Arabic operational terms across both applications. These linguistic adaptations are generated through two primary core mechanisms. Morphologically, the neologisms are predominantly formed through derivation and compounding. Semantically, the terms are constructed using metaphorical extensions of meaning (isti’arah and tawsi' al-ma'na) alongside direct translations to effectively convey digital operational functions. These findings demonstrate the Arabic language's dynamic capacity to accommodate and localize modern technological concepts within digital interfaces. The primary benefit of this thesis is to enrich the university's academic repository of knowledge, specifically to enhance students' understanding in the Department of Arabic Language and Literature of morphological and semantic studies, with a special focus on Arabic word formation related to operational terms on social media.